Measurement of the ratio B(B-s(0) -> J/psi f(0)(980))/B(B-s(0) -> J/psi phi(1020)) in pp collisions at root s=7 TeV - (:unkn) unknown (ELSEVIER, 2016)
A measurement of the ratio of the branching fractions of the B-s(0) meson to J/psi f(0)(980) and to J/psi phi(1020) is presented. The J/psi, f(0)(980), and phi(1020) are observed through their decays to mu(+)mu(-), pi(+)pi(-), and K+K-, respectively. The f(0) and the phi are identified by requiring |M-pi+(pi)- - 974 MeV| < 50 MeV and |M-K+(K)- - 1020 MeV| < 10 MeV. The analysis is based on a data sample of pp collisions at a centre-of-mass energy of 7 TeV, collected by the CMS experiment at the LHC, corresponding to an integrated luminosity of 5.3fb(-1). The measured ratio is B(B-s(0) -> J/psi f(0)) B(f(0) ->pi(+)pi(-))/B(B-s(0) -> J/psi phi) B(phi -> K+K-)= 0.140 +/- 0.008 (stat) +/- 0.023 (syst), where the first uncertainty is statistical and the second is systematic. (C) 2016 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: DECAY